PENINGKATAN KEMAMPUAN MENULIS KARANGAN DESKRIPSI DENGAN MENGGUNAKAN MEDIA GAMBAR BERSERI PADA PELAJARAN BAHASA INDONESIA SISWA KELAS III SD NEGERI 6 DAWUHAN TAHUN PELAJARAN 2017/2018 - Nur Hayati; Nani Farah Fasica (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2018)
Descriptive text has described object by using words. The description objects included person, places, events etc. The writer determined it by smell, and situation according to the object, the problem in this researh namely the students of third grade at SDN 6 Dawuhan having some problems in writing descriptive text. The students felt difficulty in choosing the word dictions. The research problem were 1) How to implement pictures series to third grade students at Bahasa Lesson in SDN 6 Dawuhan Situbondo academic year 2017/ 2018 2). Did the Implementation of pictures series improve the descriptive writing skills at third grade students in SDN 6 Dawuhan academic year 2017/2018. The type of this research is Classroom Action Research (CAR). The subjects of this research are students of Class III of State Elementary School 6 Dawuhan with 24 students, cycle is done as many as II cycle. The result of writing ability description of third grade students of SD Negeri 6 Dawuhan increased. In the implementation of pre cycle the average score of students is 43 with the category of